2017
DOI: 10.3390/ijerph14111409
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Dietary Patterns in Pregnancy: Findings from the GUSTO Cohort

Abstract: Evidence on the association between sleep, diet, and eating behaviors in pregnant women is lacking. We examine this in a cohort of apparently healthy pregnant women. At 26–28 weeks gestation, 497 participants completed the Pittsburgh Sleep Quality Index to assess sleep and a 24-h recall to assess dietary intake. Diet quality was assessed by the Healthy Eating Index for pregnant women in Singapore (HEI-SGP) score and previously derived dietary patterns (vegetables-fruit-rice, seafood-noodles, and pasta-cheese-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
2
43
1
1
Order By: Relevance
“…The current study provided new evidence of a positive association between diet quality, food diversity, and sleep quality; however, we only found a similar result in one study (van Lee et al, 2017). This study came to a conclusion that good sleep quality was associated with a better diet quality, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…The current study provided new evidence of a positive association between diet quality, food diversity, and sleep quality; however, we only found a similar result in one study (van Lee et al, 2017). This study came to a conclusion that good sleep quality was associated with a better diet quality, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…underweight) may have been too small to detect differences. A variety of relevant variables were controlled for in analyses; however, some important social and lifestyle factors, such as such as sleep quality [57], stress, depression, social support [58,59], and built environment [60], were not assessed in IFPS II and therefore, were not controlled for in analyses.…”
Section: Discussionmentioning
confidence: 99%
“…As for the daily numbers of hours sleep, we found that Chinese male and female students were found to have good habits of complete sleep (more than 6 h) as compared to international males and females students. Sleep of less than 6 hours is considered as short sleep [ 29 ]. A study found that both short and long time spent in bed and poor sleep quality is having positive relationship with overweight and obesity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%